Ageing population in Sri Lanka : issues and future prospects - Population Association of Sri Lanka; United Nations Population Fund. (Colombo : United Nations Population Fund in association with the Population Association of Sri Lanka, 2004)
On older people and government response in Sri Lanka; study emerged out of a seminar on ageing of the Sri Lankan population conducted by the PASL in collaboration with UNFPA, Colombo, 2002.
Includes bibliographical references.
Keywords: Older people -- Government policy -- Sri Lanka -- Congresses; Older people -- Government policy -- Sri Lanka -- Congresses; Population aging -- Sri Lanka -- Congresses